Implementasi Kebijakan Dana Kelurahan dalam Pembangunan Sarana Prasarana dan Pemberdayaan Masyarakat di Kelurahan Karangasem - Ida Nyoman Astawa; Ida Ayu Putu Sri Widnyani; I Made Sumada (CV. AFDIFAL MAJU BERKAH, 2024)
The central government allocates budgets to sub-districts through the Additional Allocation of General Allocation Funds (Additional DAU) scheme. At the same time, the regional government of Karangasem Regency also provides financial support to sub-districts as part of its commitment to fostering local development. The allocation of these funds is guided by Minister of Home Affairs Regulation Number 130 of 2018, which pertains to the development of sub-district facilities, infrastructure, and community empowerment. This study evaluates and analyzes sub-district fund policies' effectiveness in infrastructure development and community empowerment within the Karangasem Sub-district. Specifically, it seeks to identify whether implementing these policies is optimal and, if not, to determine the underlying causes of any sub-optimal performance and propose solutions to address these issues. The methodology employed for data analysis is qualitative descriptive analysis. The findings indicate that implementing sub-district fund policies in the Karangasem Sub-district is sub-optimal due to several impediments. According to the C. Edwards III model, only the disposition indicator is satisfactory, while communication, resources, and bureaucratic structure need improvement. Key issues include poor communication between the government and community, insufficient employee understanding of new policies, low community participation, the inadequate role of societal institutions like LPM, and the lack of standard operating procedures (SOPs) or technical guidance. Solutions include enhancing communication and coordination, providing training and educational opportunities, encouraging community involvement, and strengthening the role of societal institutions.